Nurse's Knowledge About Ewss In Adult Patients Based On Characteristics In The Room Critical Hospital Of Santa Elisabeth Medan - Nagoklan Simbolon; Hilarius Hendra Ridho Dachi (Sean Institute, 2022)
Lack of knowledge about EWSS causes nurses to be unable to detect a decrease in the patient's clinical condition which has an impact on the patient's poor condition, resulting in respiratory or cardiac arrest which results in delays in providing help, which in turn increases mortality. Nurse knowledge is one of the influencing factors for detecting patients in hospitals. Nurses' knowledge affects their ability to identify patients with worsening patient conditions. The purpose of this study was to describe the knowledge of nurses about EWSS in adult patients based on characteristics in the Critical Room of Santa Elisabeth Hospital Medan 2022. The research method used was descriptive. The population is 60 people with a sample of 30 people taken proportionally. The results showed that respondents' knowledge was more in sufficient categories, namely: age 31-40 years by 46.6% and the lowest with good knowledge 6.7%, female sex more by 60% and male with low knowledge 3.3%. The highest education is D3 Nursing 43.3% and the lowest is S1 Nursing 16.6%, the highest length of work is >5 years 50% and the lowest is 1-3 years 6.6%. The conclusion that the highest knowledgeable enough was based on the age of 31-40 years was 46.6%, the highest gender was female 60%, the highest education was D3 Nursing at most 43.3%, and the highest length of work >5 years was 50%. It is recommended to the Management of Santa Elisabeth Medan House to provide EWSS training for those who have never been trained and who have received training for new nurses, and nurses who have been for a long time and have received training on EWSS so that they can be refreshed so that nurses' knowledge can still be improved.